Framing analysis on the news coverage of online sunstar Philippines on the Marawi conflict - Alaman, Safora Korina P. (2019)
It has always been a challenge for the media to cover news on war stories in a manner that will not further spur panic among the citizens. According to communication scholars, the reporters? own biases on the news greatly impact the way that this news are being framed which eventually shapes the public opinion. Thus, it was the purpose of this study to determine whether the news about the Marawi conflict in 2017 was framed in peaceful or war orientation. News articles were analyzed through a framing method based on an operalisation by Johan Galtung. Each news part was given a positive one (1) point if it was conflict-oriented and a negative one (1) point if it was violence-oriented. Then, the frequencies of each frames and keywords were measured through the mode. The data was qualitatively described according to the codes provided by Galung?s operalisation. It was determined that Sunstar Philippines dominantly used peace framing on the crisis. It shifted though into war orientation from September until October which marked the end of the war. This study hoped to impart a substantial contribution to further understand media?s news framing techniques that help shape public opinion, biases, decision-, and even policy-making.